Thermal management in electronic packages - Mena, Manolo G. (Philippine Engineering Journal)
Packaging of an integrated circuit not only involves the physical isolation of the delicate integrated circuit or "silicon chip" from the environment but also the provision of a thermal conduction path to allow the heat generated during the operation of the chip to be dissipated to the environment. This paper presents the various types of failures accelerated by an increase in temperature of the integrated circuit and the modes of heat transfer through the packaging material. Characterization of the thermal characteristics of IC packages through the use of "thermal resistances" in also presented.